Relationship Duration of Treatment Between Anxiety in a Child with Cancer During Chemotherapy - Wahyudi, Totok; Utomo, Endrat Kartiko; Marhamah, Lin; Kartikasari, Annisa Yuli (Nursing Genius Journal, 2024)
Cancer is the second-leading cause of death (after accidents) in children between the ages of 5 and 14 years old. Cancer can cause psychosocial anxiety problems that can lead to psychological problems that affect adulthood. The aim of this study is to find out the long-standing relationship between the treatment of anxiety and cancer in a child who will undergo chemotherapy at Dr. Moewardi Surakarta. This research method uses a cross-sectional design. Sampling using a non-probability sampling technique with a consecutive sampling method with a sample number of 30. The measurement tool uses a questionnaire that has been tested for validity and reliability by previous researchers, namely an emergency questionnaire by Aidar (2011) with 10 subjects matching the criteria using a competition application with a cronbach alpha analysis of 0.862. The results of the statistical tests showed that there was no long-term meaningful relationship between treatment and anxiety (p = 0.595).